An Examination of the Context-Linked Influences on the Achievement Outcomes of African American Male High School Seniors. Issue 2 (25th February 2022) - Clayton, M Annette; Teasley, Martell L
Abstract: Although students must successfully navigate transition years in school in pursuit of sustained academic success, not enough is known about the context-linked experiences of African American male adolescents as they seek to traverse their senior year, one of the most important pivotal points in time for all students. This study examined the relationship between perceptions of support from significant others, exposure to contextual risks, and two achievement outcomes in a representative sample of 139 African American male high school seniors. At this critical juncture in their education career, teacher support was predictive of higher grade point average (GPA), and a specific type of family support was associated with lower GPA. Qualitative analysis revealed similarities and differences in types of support reported to have had an impact on the participants' success in school. Results from the study confirm one hypothesis that exposure to contextual risks predicts poorer achievement outcomes. Findings affirm the need for tailored interventions that target and strengthen the systems of support within the social environment of academically at-risk African American male students.